Mixed Artificial Diets Enhance The Developmental And Reproductive Performance Of The Edible Grasshopper, Ruspolia Differens (Orthoptera: Tettigoniidae) - Malinga, Geoffrey M.; Valtonen, Anu; Lehtovaara, Vilma J.; Rutaro, Karlmax; Opoke, Robert; Nyeko, Philip; Roininen, Heikki (Applied Entomology and Zoology, 2018)
Diet mixing is a common feeding habit among polyphagous insect herbivores and is believed to be advantageous for performance-related factors like growth, survival and oviposition. However, relatively little is known about the influence of artificial diet or their mixtures on the performance of edible insects. We examined the effects of artificial diet mixtures on the developmental and reproductive performance (survival, developmental time, fresh adult weight and female fecundity) of an edible grasshopper, Ruspolia differens (Orthoptera: Tettigoniidae). We raised individuals from eggs and reared newly hatched nymphs to adult stage on six different dietary treatments consisting of a single diet, and mixtures of two, three, five, six and eight artificial diets. More diversified diets resulted in shorter development time and greater adult fresh weight and female fecundity compared to the single diet or less diversified diets. Even with slight diet diversification, survival to adult stage was greatly improved. Overall, these results highlight the potential of diet mixtures in achieving maximum adult weights and female fecundity and shortening development time, information which could be used when designing mass-rearing programs for this edible grasshopper.
Keywords: African edible bush cricket · Captive rearing · Diet mixing · Insect farming · Mass rearing